Cash Waqf Model for Social Enterprise to Achieve Sustainable Development Goals in Indonesia - Najim Nur Fauziah; Salina Kassim (AL-MUZARA'AH, 2022)
Social enterprises are expected to bring significant positive impact on Indonesia's economy and may help to meet the Sustainable Development Goals (SDGs). Social enterprises empower minorities by providing more opportunities for a sustainable means of livelihood, especially for low-income and disadvantaged groups. However, despite its potential, financial issues remain a significant barrier for the viability of social enterprises in Indonesia. Cash waqf is one of the Islamic social finance vehicles that can be used to invest and manage funds to address a variety of social issues related to the SDGs. Hence, this study aims to propose cash waqf model for social enterprise in achieving the SDGs in Indonesia and to assesses the potentials and opportunities of developing the proposed model in Indonesia. This study employs a qualitative research approach, with primary data gathered from interviews of relevant stakeholders. This study finds that, the cash waqf can solve a multitude of financial issues faced by many social enterprises in Indonesia by enlarging their pool of financing support. The possibilities and opportunities of developing the cash waqf model for social enterprise include alternative funding for social enterprise, alternative waqf for waqif, an increase in nazhir, and more effective contribution to the SDGs.